Cardiac Rehabilitation During the COVID-19 Era: Guidance on Implementing Virtual Care - Moulson, Nathaniel; Bewick, David; Selway, Tracy; Harris, Jennifer; Suskin, Neville; Oh, Paul; Coutinho, Thais; Singh, Gurmeet; Chow, Chi-Ming; Clarke, Brian; Cowan, Simone; Fordyce, Christopher B.; et al. (Canadian journal of cardiology, 2020)
Cardiac rehabilitation programs across Canada have suspended in-person services as a result of large-scale physical distancing recommendations designed to flatten the COVID-19 pandemic curve. Virtual cardiac rehabilitation (VCR) offers an alternate mechanism of care delivery, capable of providing similar patient outcomes and safety profiles compared with centre-based programs. To minimize care gaps, all centres should consider developing and implementing a VCR program. The process of this rapid implementation, however, can be daunting. Centres should initially focus on the collation, utilization, and repurposing of existing resources, equipment, and technology. Once established, programs should then focus on ensuring that quality indicators are met and care processes are protocolized. This should be followed by the development of sustainable VCR solutions to account for care gaps that existed before COVID-19, and to improve cardiac rehabilitation delivery, moving forward. This article reviews the potential challenges and obstacles of this process and aims to provide pragmatic guidance to aid clinicians and administrators during this challenging time. En raison des recommandations concernant l’éloignement physique à grande échelle visant à aplatir la courbe pandémique de la COVID-19, tous les services offerts en personne dans le cadre de programmes de réadaptation cardiaque au Canada ont été suspendus. La réadaptation cardiaque virtuelle (RCV) constitue une solution de rechange pour la prestation des soins, dont les résultats pour les patients et les profils d’innocuité se comparent à ceux des programmes offerts en établissement. Afin de réduire le plus possible l’interruption ou le report des soins, tous les établissements devraient envisager de mettre au point et d’instaurer un programme de RCV. La mise en œuvre rapide d’un tel programme peut toutefois être intimidante. Il faut d’abord se concentrer sur la compilation, l’utilisation et le recyclage des ressources, des technologies et de l’équipement existants. Une fois les programmes en place, il faut veiller à ce que les critères de qualité soient satisfaits et à établir des protocoles pour la prestation des soins. Vient ensuite la mise au point de solutions de RCV durables comblant les lacunes qui existaient avant la COVID-19 et améliorant la prestation des soins de réadaptation cardiaque. Les auteurs passent en revue les défis et les obstacles potentiels d’une telle entreprise et tentent de formuler des conseils pragmatiques pour aider les cliniciens et les administrateurs en ces temps difficiles.